PEMANFAATAN TEKNOLOGI INFORMASI BERBASIS WEBSITE DAN ANDROID SEBAGAI MEDIA PELAPORAN DAN PROMOSI ANTINARKOBA : LITERATURE REVIEW - Akbar Suseno; Sukihananto (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2023)
Background :Information technology is needed in today's era to support the dissemination of certain information. Utilization of website and android-based information technology can be used for media reporting and health promotion facilities. Objective: This study aims to analyze and design website and android-based information technology as a medium for reporting and promoting drugs at the Recipient Institution of Compulsory Reporting (IPWL) at the Regional Hospital of Jambi Province. Method : This study uses a literature review method. Result: This research resulted in website collaboration technology with android to create mobile applications in providing drug promotion (education) to the public about the dangers of drugs, and reporting data for IPWL officers. Conclusion: The results of this study are intended to assist parties involved in the drug eradication movement in Indonesia. Keywords: Reporting, Promotion, IPWL, Website, Android, Information Technology